EMPLOYEES’ SHARING IN DECISION MAKING: A STUDY OF ARAB POTASH COMPANY IN JORDAN - Al Kalaldeh, Taher (European Scientific Journal, ESJ, 2013)
Aim: to assess the perception of employees towards sharing in decision making in one of the largest industrial company in Jordan. Background: sharing employees in decision making is seen to promote cooperation, enhance employees’ capabilities, and support productivity. Studies found that employees’ sharing entails reduction in cost of both monitoring and supervising employees in addition; motivation is enhanced when performance is reinforced. Method: the descriptive correlational design was used through seeking employees from different administrative levels. Employees participated in the study completed a pre-prepared self-administered questionnaire which consists of a number of aspects surrounding employees’ sharing in decision making. Findings: A total of 151 participants joined the study. The study showed low-to-moderate level of employees’ sharing in managerial decisions. Employees perceived themselves competent to share in working decision. Employer’s seriousness, time allowance, and presence of incentives were factors perceived to be impetus towards promoting employees’ sharing. Conclusion: management should not be reluctant to enhance sharing of employees that can promote best organizational performance.